رستەى شوێنکەوتووى ئەنجام و ڕستەى شوێنکەوتووى ئاگادارکردنەوە - عەلى, بەکر عومەر (Sulaimani Journal for Humanities, 2003)
This research deals with two kinds of complex sentence in Kurdish language. So far, nothing has been written about the second kind and perhaps only one paper is found dealing with the first. In this research, we discuss both kinds in detail, shedding light on their features. It is worth mentioning that up to this moment, there is no statistics about conjunctions in Kurdish language. The research also specifies some of these conjunctions. Finally, the paper is part of the many attempts to compose a Kurdish grammar.